Association Between Sleep Characteristics and Likelihood of Prodromal Parkinson’s Disease: A Cross-Sectional Analysis in the HABIT Study - Mao CJ; Peng H; Zhuang S; Zhang YC; Xie WY; Yan JH; Liu HH; Chen J; Liu JY; Zhang J; Jiang H; Zhang Y; et al. (Nature and Science of Sleep, 2024)
Cheng-Jie Mao,1,* Hao Peng,2,* Sheng Zhuang,1,* Ying-Chun Zhang,3 Wei-Ye Xie,1 Jia-Hui Yan,1 Hui-Hui Liu,1 Jing Chen,1 Jun-Yi Liu,4 Jianan Zhang,5 Hai Jiang,5 Yonghong Zhang,2 Mingzhi Zhang,2 Chun-Feng Liu1,6 1Department of Neurology and Clinical Research Center of Neurological Disease, The Second Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China; 2Department of Epidemiology, School of Public Health, MOE Key Laboratory of Geriatric Diseases and Immunology, Suzhou Medical College of Soochow University, Suzhou, People’s Republic of China; 3Department of Ultrasound, The Second Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China; 4Department of Neurology, The Fourth Affiliated Hospital of Soochow University, Suzhou, People’s Republic of China; 5Department of Chronic Disease, Taicang Center of Disease Prevention and Control, Suzhou, People’s Republic of China; 6Institute of Neuroscience, Soochow University, Suzhou, People’s Republic of China*These authors contributed equally to this workCorrespondence: Chun-Feng Liu, Department of Neurology and Clinical Research Center of Neurological Disease, the Second Affiliated Hospital of Soochow University, 1055 Sanxiang Road, Suzhou, 215004, People’s Republic of China, Email liuchunfeng@suda.edu.cn Mingzhi Zhang, Department of Epidemiology, School of Public Health, Medical College of Soochow University, 199 Renai Road, Industrial Park, Suzhou, 215123, People’s Republic of China, Email zhangmingzhi@suda.edu.cnBackground: Sleep is critical in health problems including Parkinson’s disease (PD). This study examined the association between sleep characteristics and the likelihood of prodromal PD.Methods: At baseline examination of the Heart and Brain Investigation in Taicang (HABIT) study, potential PD biomarkers were obtained for 8777 participants aged over 50 years, and the probability of prodromal PD was assessed based on the Chinese expert consensus and Movement Disorder Society (MDS) criteria. General and component sleep characteristics were evaluated by the Pittsburgh Sleep Quality Index (PSQI). Median regression was applied to examine the association between sleep and the probability of prodromal PD, adjusting for age, sex, education level, physical activity, obesity, fast plasma glucose, lipids, and hypertension.Results: Based on China criteria, a higher level of PSQI score was significantly associated with a higher probability of prodromal PD (β = 0.02, 95% CI: 0.01– 0.03) and a higher risk of having an increased probability of prodromal PD (OR = 1.04, 95% CI: 1.02– 1.05). Compared to participants with good quality sleep, those with poor quality sleep had a 0.07% increased probability of prodromal PD (95% CI: 0.01– 0.13) and a 19% increased risk of having a high prodromal PD probability (95% CI: 1.04– 1.20). Similar associations between sleep quality and the probability of prodromal PD were also observed using the MDS criteria. Subjective sleep quality, sleep latency, habitual sleep efficiency, daytime dysfunction, and use of sleep medications were also associated with the probability of prodromal PD.Conclusion: Poor sleep quality was associated with a high probability of prodromal PD. Sleep may be helpful for understanding and intervention of prodromal PD.Keywords: prodromal Parkinson’s disease, sleep, Parkinson’s disease